Transmedia storytelling and the creation of a converging space of educational practices - Rodrigues, Patrícia (2015)
As the media landscape evolves, educators are tapping into learning opportunities that meet the needs of 21st century learners. This paper provides an entry point to a relevant social problem related to education with Trans- media Storytelling, a story that crosses multiple forms of media, and each delivers a unique or specific contribution to the story experience. This study aims to contribute to the development and application of Transmedia Storytelling in educational settings. For this purpose a set of frameworks and educational models were selected based on research that points to the widespread use of transmedia learning experi- ences that are authentic, engaging, immersive, as well as support the development of new literacies. Ultimately, we attempt to demonstrate how the creation of a transmedia learning environment will allow the learner to develop and thrive in the digital age.